Cerebral malaria in children. - Phillips, R; Solomon, T (1990)
Cerebral malaria is a rapidly progressive encephalopathy with up to 50% mortality. A cardinal feature is the massing of red cells containing mature Plasmodium falciparum within the cerebral capillaries. Adhesion of these parasitised red cells to endothelium, an event which may initiate cerebral malaria, is being studied at the molecular level. However, the relevance of these studies to the pathophysiology and treatment of human cerebral malaria is uncertain. Although chloroquine is still widely used to treat falciparum malaria, resistance has spread to most of the endemic zone. Quinine is emerging as the only effective treatment for cerebral malaria, though resistance to this drug threatens to become a problem. Alternative drugs are urgently needed.